Dynamics of the human gut phageome during antibiotic treatment. (June 2018) - Górska, A.; Peter, S.; Willmann, M.; Autenrieth, I.; Schlaberg, R.; Huson, D.H
Abstract: Bacterial viruses contribute to the dynamics of the microbiome communities, as they are involved in the horizontal gene transfer. Previously we studied changes in the gut microbiome of the two healthy individuals over the course of a 6-days antibiotics treatment and subsequent 28 days recovery time (Willmann et al., 2015). Now, from the same samples, the virus-like particles were isolated and sequenced. As the phage sequences are currently poorly represented in reference databases, the reads had to be assembled, annotated and their abundance had to be evaluated via reads mapping. We analyzed and compared patterns of changes in abundance of the phage scaffolds and scaffolds with antibiotics resistant genes, in both phage and whole-genome metagenomic sets. We observed an increase in abundance of scaffolds carrying antibiotic-resistant genes in response to the treatment.